Vocabulary tools for the improvement of the speaking skills in students of eighth grade at escuela de educación básica superior Teodoro Wolf, Santa Elena, province of Santa Elena, school year 2016-2017. - Muñóz Ruidiaz, Karina Alexandra (2016)
This research paper investigated how English language learners reacted to the implementation of pedagogical resources in order to improve their speaking skill in the classroom. The implementation of vocabulary tools was the primary resource which contributed to provide new strategies in the process of learning and teaching in the classroom. It is suggested that the use of this kind of resources causes impact on English education process in general. This project should be implemented so that students could feel motivated to develop their speaking skills. In this study, pedagogical options motivated to students to be continuously engaged. To this project English teacher has a relevant role of guide and she should keep the interaction between students during the learning process. The participants of this qualitative study were observed during the different classes, the data was gathered from observations, focus groups and interviews. Speaking is an essential skill which could be developed through using vocabulary tools which promote the enhancement of this skill. Using vocabulary tools is one effective way to integrate pedagogical activities during the process of learning. The present research shows the improvement of the speaking skill of the eighth grade students from Escuela de Educación Básica Teodoro Wolf with the help of vocabulary tools, especially for this study designed in which through a series of activities that engaged in speaking activities in an enjoyable way.